2015
DOI: 10.3168/jds.2014-8858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a high-energy diet on oocyte quality and in vitro embryo production in Bos indicus and Bos taurus cows

Abstract: The effects of different dietary energy levels [100 and 170% for maintenance (M) and high energy (1.7M), respectively] on metabolic, endocrine, and reproductive parameters were evaluated in nonlactating Bos indicus (Gir; n=14) and Bos taurus (Holstein; n=14) cows submitted to ultrasound-guided ovum pick-up followed by in vitro embryo production. The oocyte donor cows were housed in a tiestall system and fed twice daily (0800 and 1600 h). Twenty-one days before the beginning of the experiment, the animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 58 publications
8
47
1
11
Order By: Relevance
“…Success in in vitro bovine embryo production is directly related to the quality of the gametes used, which is largely influenced by nutrition (Sales et al, 2015). In general, oocyte donors receive a controlled diet without significant changes in quantity and composition throughout the year, which makes it a negligible factor in the variation of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Success in in vitro bovine embryo production is directly related to the quality of the gametes used, which is largely influenced by nutrition (Sales et al, 2015). In general, oocyte donors receive a controlled diet without significant changes in quantity and composition throughout the year, which makes it a negligible factor in the variation of the process.…”
Section: Discussionmentioning
confidence: 99%
“…More oocytes were recovered (37.1 vs. 15.4), more embryos were produced (7.3 vs. 1.1), and a greater blastocyst rate was obtained (28.3 vs. 14.1%) from Nelore than Holstein heifers. In another study (Sales et al, 2015), Gir cows had a greater number of oocytes recovered by ovum pickup (OPU; 23.4 vs. 14.9), better quality of oocytes demonstrated by greater cleavage rates (73.6 vs. 40.8%), greater number of blastocysts (3.8 vs. 0.7) and better blastocyst rates (36.7 vs. 12.1%) than Holstein donors.…”
Section: Practical Implications Of the Physiological Differences Betwmentioning
confidence: 99%
“…Interestingly, supplementation of sunflower seeds or sunflower oil had a positive effect on milk yield and milk composition in lactating goats (Morsy et al, 2015). Although having an association with bronchiolitis (Sawahata et al, 2010) and cytotoxic activity (Yunita et al, 2013), Sauropus androgynus is traditionally consumed by several Southeast Asian countries and is believed to be an enhancer of milk production during lactation (Bunawan et al, 2015). When feeding S. androgynus leaf extract to lactating mice, it enhanced the expression of two prominent genes (prolactin and oxytocin) regulating milk production and subsequently, increased milk production (Soka et al, 2010) suggesting their potential use to increase milk production in livestock ruminants (Gabbi et al, 2015).…”
Section: Milk Productionmentioning
confidence: 99%
“…Interestingly, Sales et al, found different dietary energy levels have no influence on the oocyte numbers and quality. In addition, high energy diet intake for a long period may decrease the in vitro production of embryos in Bos indicus cows by causing a hyperinsulinemic state and inducing the downregulation of cellular metabolism genes (Sales et al, 2015).…”
Section: Enhance Reproductive Performancementioning
confidence: 99%